2014
DOI: 10.3109/08880018.2014.930766
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Efficacy in the Treatment of Children with Chronic Immune Thrombocytopenic Purpura

Abstract: The results of this study demonstrate proper safety of Rituximab in the treatment of chronic ITP. However, the drug had no significant effect on the expected improvement in platelet count of patients. It seems that monotherapy is ineffective in the treatment of chronic ITP and combination with other complementary therapies is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An increased incidence of bacterial infection is also reported in adults treated with rituximab for autoimmune diseases; the presence of diabetes and contemporary use or/and prednisone is a further risk factor. 80 , 81 Hypogammaglobulinemia has also been reported among adults and children, 76 although the overall number is unclear and appears to occur with repeated doses and in patients with underlying immune dysfunction. Studies have shown impaired humoral responses to vaccination after rituximab.…”
Section: Late Infectionsmentioning
confidence: 99%
“…An increased incidence of bacterial infection is also reported in adults treated with rituximab for autoimmune diseases; the presence of diabetes and contemporary use or/and prednisone is a further risk factor. 80 , 81 Hypogammaglobulinemia has also been reported among adults and children, 76 although the overall number is unclear and appears to occur with repeated doses and in patients with underlying immune dysfunction. Studies have shown impaired humoral responses to vaccination after rituximab.…”
Section: Late Infectionsmentioning
confidence: 99%
“…Three studies (two for eltrombopag and one for romiplostim) were shown to have a low risk of all types of bias analyzed 16,31,32 . The amount of missing information varied across the other studies, 17–25 but the highest overall bias for missing data was found in several of the RTX studies, 37,38 including missing data regarding the association between the intervention and severity of bleeding. Although it is not among the criteria for assessment of risk, it is important to note that some studies were supported by the pharmaceutical industry, with the potential for bias due to conflict of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Rituximab, an anti‐CD20 monoclonal antibody, has also been used as treatment for both persistent/chronic ITP and AIHA in children and adults. For ITP, initial response rates vary greatly, but prolonged remission beyond 1 year is less than 50%, as evidenced by multiple studies . A recent article evaluated the long‐term response rates in a 5‐year follow‐up study for both adults and children, which showed a continued response in only 21 and 26%, respectively .…”
Section: Discussionmentioning
confidence: 99%